MANNONI, Maud. Educação impossível. Rio de Janeiro: Francisco Alves, 1988. - de Holanda, M Júlia B. (Educação Por Escrito, 2014)
MANNONI, Maud. Educação impossível. Rio de Janeiro: Francisco Alves, 1988. 320p.